Makna Leksikal, Makna Kultural, dan Kearifan Lokal dalam Leksikon Peternakan Sapi Perah di Kecamatan Cepogo, Kabupaten Boyolali - Yordania, Brenzila Rendy; Fateah, Nur (Stilistika: Jurnal Pendidikan Bahasa dan Sastra, 2024)
Every field of work typically has its own specialized lexicon that is frequently used, including in dairy cattle farming. This research aims to analyze the lexical meaning, cultural meaning, and local wisdom of the lexicon related to dairy cattle farming using lexical, cultural, semantic, and anthropolinguistic theories. The method used is descriptive qualitative. The data sources for this study are 8 people from the community in Cepogo District, Boyolali Regency, who work as dairy farmers. Data collection was conducted through several methods, including observation, interviews, as well as note-taking and recording techniques. Then, data triangulation was performed. The data obtained consists of the lexicon related to dairy cattle farming, which was then analyzed based on semantic and anthropolinguistic studies. Based on the research results, it can be concluded that each analyzed lexicon reflects social and economic impacts, interactions between livestock and humans, and farmers' knowledge to improve livestock productivity.